2018
DOI: 10.1007/s12032-018-1114-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of purple carrot extract (Daucus carota) against rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide

Abstract: The aim of this study was to evaluate the chemopreventive potential of purple carrot extract following rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide (4NQO). For this purpose, histopathological analysis, proliferative status, antioxidant activity and inflammatory status were investigated in this setting. A total of 20 male rats were distributed into four groups as follows (n = 5 per group): Group 1-free access to water and commercial diet for 12 weeks; Group 2-received 4NQO at 50 ppm dose in dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Upon euthanization; tongues had normal histological features with no inflammatory, or atypical changes. These results were in agreement with other studies that reported the same findings on control group when the same model was used (4,19) .…”
Section: Discussionsupporting
confidence: 93%
“…Upon euthanization; tongues had normal histological features with no inflammatory, or atypical changes. These results were in agreement with other studies that reported the same findings on control group when the same model was used (4,19) .…”
Section: Discussionsupporting
confidence: 93%
“…In oral cancer patients, elevated salivary 8OHdG levels have already been related to tumor progression and also seem to be involved in the pathogenesis of the disease 30 , 31 . The increased 8OHdG immunoexpression in non-tumor tissues contribute to the chemical oral carcinogenesis in preclinical models 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was made according to Soares et al 26 For this, serial sections of 4 μm were deparaffinized in xylene, rehydrated in ethanol, and incubated in a microwave with 10 mM citric acid buffer (pH = 6) for three cycles of 5 minutes each for antigen retrieval. The following primary antibodies were used: matrix metalloproteinases-2 (MMP-2) mouse monoclonal anti-rat antibody (1:50) (8B4), MMP-9 mouse monoclonal anti-rat antibody (1:100) (2C3) and 8-hydroxydeoxyguanosine (8OHdG) mouse monoclonal anti-rabbit antibody (1:100) (B1712) Santa Cruz Biotechnology, CA.…”
Section: Immunohistochemistrymentioning
confidence: 99%